EFEKTIVITAS PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DI DESA PAMEUTINGAN KECAMATAN CIPATUJAH KABUPATEN TASIKMALAYA - Dasep Dodi Hidayah (UNIVERSITAS ISLAM SYEKH YUSUF, 2020)
This study aims to study and explain the level of planning for the implementation of development planning deliberations in Pameutingan Village, Cipatujah District, Tasikmalaya Regency. The Musrenbang in Pameutingan Village, Cipatujah Subdistrict, is still not optimal. With research methods that use research by using descriptive research methods for qualitative, and deepening the data collection techniques used to use observation, interview and documentation techniques. From this study are the results that show the Effectiveness of Musrenbang Implementation in Pameutingan Village, Cipatujah District, Tasikmalaya Regency based on the dimensions of goal achievement, integration and adaptation that have not been well implemented. Keywords: Effectiveness, Development Planning, Participation